La Revista de la Escuela Superior de Guerra "Tte Grl Luis María Campos" ; no. 590/2015 - Escuela Superior de Guerra Tte Grl Luis María Campos (Argentina) (2015)
Ejemplar: Revista de la ESG. Año 93, no. 590 (may-ago. 2015). 165 p.